ANALYSIS OF CHILD CUSTODY (HADHANAH) AFTER DIVORCE FROM THE PERSPECTIVE OF DHARURIYAH - Meilan Lestari, (Proceeding International Conference on Social Sciences, 2026)
Divorce is the dissolution of the physical and spiritual bond between husband and wife in building a happy and everlasting household based on the belief in Almighty God. Divorce is an act that is permitted but disliked by Allah, as it has a significant impact on family life, particularly on children. Children are a trust (amanah) given by Allah to their parents, entrusted to their care so that they may receive complete love and affection from both parents. Every child has the right to be educated, cared for, and nurtured by both parents, both in general and in accordance with religious teachings. Through religious education, a child becomes closer to Allah. Child custody (hadhanah), according to Article 1 paragraph (g) of the Compilation of Islamic Law, refers to the activity of caring for, maintaining, and educating a child until he or she reaches maturity and can manage his or her own affairs. The Qur’an also explains that as servants of Allah and believers, we are obliged to protect ourselves and our families (our children) from the fire of Hell. This is intended so that the children we raise become faithful and pious to Allah and His Messenger, and are not led astray into acts that incur Allah’s wrath. Instilling religious values in children from an early age is crucial so that they can protect and preserve their own faith, soul, and intellect. This will allow them to have peace of mind and sound reasoning, and to avoid moral damage or deviance resulting from the divorce of their parents.